Mixed media sand painting / Mohd Al Amin Md Kahir - Md Kahir, Mohd Al Amin (Universiti Teknologi MARA, Kedah, 2018)
A mixed media painting is one which combines different painting adn drawing materials and methods, rather than only one medium. Any materials can be used, including collage items such as pages from magaines, newpaper, photographs, fabric, soil, or packaging. Or a mixed media piece can be as 'simple'as using two mediums, such as acrylic paints with pastel on top.